Does Kisspeptin Signaling have a Role in the Testes? - Hua, Mei; Doran, Joanne; Kyle, Victoria; Yeo, Shel-Hwa; Colledge, William H. (Frontiers in Endocrinology, 2013)
Kisspeptins are a family of overlapping neuropeptides encoded by the Kiss1 gene that regulate the mammalian reproductive axis by a central action in the hypothalamus to stimulate GnRH release. Kisspeptins and their receptor (Gpr54 also called Kiss1r) are also expressed in the testes but a functional role in this tissue has not been confirmed. We examined which cell types in the testes expressed kisspeptin and its receptor by staining for β-galactosidase activity using tissue from transgenic mice with LacZ targetted to either the Kiss1 or the Gpr54 genes. Expression of both genes appeared to be restricted to haploid spermatids and this was confirmed by a temporal expression analysis, which showed expression appearing with the first wave of haploid spermatid cells at puberty. We could not detect any kisspeptin protein in spermatids however, suggesting that the Kiss1 mRNA may be translationally repressed. We tested whether kisspeptin could act on Leydig cells by examining the effects of kisspeptin on the immortalized Leydig cell line MA-10. Although MA-10 cells were shown to express Gpr54 by RT-PCR, they did not respond to kisspeptin stimulation. We also tested whether kisspeptin could stimulate testosterone release by a direct action on the testes using explants of seminiferous tubules. The explants did not show any response to kisspeptin. The functional integrity of the MA-10 cells and the seminiferous tubule explants was confirmed by showing appropriate responses to the LH analogue, human chorionic gonadotrophin. These data suggest that kisspeptin signalling does not have a significant role in testes function in the mouse.